What Makes Developing Asia Resilient in a Financially Globalized World? - Hiro Ito; Juthathip Jongwanich; Akiko Terada-Hagiwara (Asian Development Bank (ADB), 2009)
The pullbacks of capital inflows to developing Asia following the onset of the global financial crisis in 2008 have brought renewed attention to the role and benefits of financial globalization. A number of notable distinctions between the current global crisis and the Asian financial crisis have become evident. Solid domestic institutions, especially in the financial sector; swift policy responses; and a sound macroeconomic environment with adequate reserves have helped the region to manage well the adverse impacts of the global crisis. Empirical analysis examining the link between capital account openness and output volatility reveals that a developing country with a more open capital market tends to experience lower output volatility, contrary to what might be expected. It is also found that countries can mitigate the destabilizing effect of pursuing greater exchange rate stability by holding a sufficiently high level of foreign reserves. Furthermore, if they want to reap the benefit of financial liberalization to reduce output volatility, highly integrated economies need to be equipped with highly developed financial markets, particularly of banking and stock markets.
hdl:11540/1845
Keywords: 330; financial globalization; capital markets; financial integration; economic stability